ENERGY COMMUNITY POTENTIAL MANAGEMENT - Dykan, Valeriia; Bilous, Liliia (Social Economics, 2018)
The article describes the main tendencies of the country's development in the direction of energy savingin the conditions of decentralization and reveals the state of implementation of the energy reform of Ukraine and highlights the place of the communities in implementing the Association Agreement. In particular, the state of creation of the fund for energy efficiency is considered. It is determined that the basis of energy security of the state is the reliable and efficient functioning of the fuel and energy complex. A complex analysis of the power structures of the power generating stations of Ukraine has been carried out. In addition, the dynamics of total electricity consumption in the three years (2015-2017) is analyzed, as well as indicators of consumption by industries. The basic problems, which have a negative influence on the tendencies of development of the energy sector and weaken the energy security of the state, are determined. It is noted that energy saving and resource conservation are the main global trends at the moment, and the strategic goals of Ukraine's development are set in accordance with the national report for 2017, such as affordable and clean energy and responsible consumption and production [16]. The article analyzes electricity consumption in Novovodolazhskaya OTG of Kharkiv region. For example, the community of the region highlights the urgent problems that face the community every day in need of resolution. The author gives recommendations that will help to optimize energy consumption and reduce the cost of the population. In addition, it is noted that. there is a need for measures to increase the efficiency of the use of thermal energy, as well as conducting educational activities on ways to save energy, which will reduce the voltage on the gri.